INFLUENCE OF HUMILID DRUG ON THE QUALITY OF SPERM PRODUCTION IN BREEDING BOARS UNDER DIFFERENT REGIMES OF USE - Stepchenko, Lilia; Pavlova, Inga; Chukhlib, Yevgen (Translational Research in Veterinary Science, 2021)
Background: Studies have shown the influence of the Red and White Belted meat breeding boars’ usage regimes on the quality of sperm products under the effect of “Humilid” biologically active feed supplement. The data obtained in the control group of breeding boars are explained by their intensive use and significant consumption of body resources to maintain sexual activity. Due to the adaptogenic properties of the drug, which had a positive effect on the quality of sperm production in the experimental group of animals on the 30th day of the experiment, the body’s resources were mobilized. It is established that consumption of biologically and ecologically safe feed supplements of humin nature permits to obtain high-quality and complete sperm products under different regimes of using breeding boars. Methods: For the experiment, 10 animals of similar age and live weight were selected, 5 of which were the control group that did not receive the ’Humilid’ drug and 5 animals that received a biologically active feed supplement with food. During the experiment, different regimes of boar usage were applied (once, twice and three times a week) for 60 days. The experiment was divided into three stages (preparatory, main, and final), during which sperm quality indices were monitored: ejaculate volume, sperm concentration, total number, and number of live sperm, their motility, and survival during incubation. Results: In the previous period, the following dynamics in the effect of the effect of the regimens on sperm quality was observed: the twofold regime showed a decrease in ejaculate volume in the control group by 18.7 % and in the experimental group by 7.2 % compared to a single semen collection regimen. In the main period, the decrease in ejaculate volume was 17.6 % (p<0.001) and 5.4 % (p<0.001), respectively, and at the final stage – by 15.8 % (p<0.001) and 9.1 % (p<0.001). At that time, sperm motility and survival rates were the highest in animals that received “Humilid” biologically active feed supplement and had a sexual load twice a week. Sperm motility in the preparatory period in the control group was 90.4 % and in the experimental group – 95.0 %, survival – 84.0 % and 90.8 %, respectively. During the main phase of the experiment, sperm motility was within the range of 85.9 % and 98.8 % and survival – 78.5 % and 95.3 %, respectively. In contrast, in the final stage, sperm motility was 89.6 % and 92.0 % and survival was 82.0 % and 88.9 %, respectively.